Influencer marketing for dummies - Sammis, Kristy, ....-; Lincoln, Cat, ....-; Pomponi, Stefania, ....- (Hoboken, N.J. : John Wiley & Sons, 2016)
The easy way to get 'in' with influencer marketingAre you a marketing guru looking to stay at the top of your game? Then you need to be in the know on influencer marketing. A hybrid of content marketing and native advertising, influencer marketing is an established trend in marketing that identifies and targets individuals with influence over potential buyers. Although this has usually meant focusing on popular celebrities and Internet personalities, there is a new wave of 'everyday consumers' that can have a large impact. InInfluencer Marketing For Dummies, you'll find out how to market to those who rock social media—and, subsequently, grow your brand.
Keywords: Influencer